2021
DOI: 10.1007/s00296-021-04803-9
|View full text |Cite
|
Sign up to set email alerts
|

Risk and clinical outcomes of COVID-19 in patients with rheumatic diseases compared with the general population: a systematic review and meta-analysis

Abstract: Patients with rheumatic diseases are often more susceptible to different bacteria and viruses because of immune impairment, but it is not clear whether there is a higher risk of infection and a more serious course of disease for novel coronavirus (SARS-CoV-2). We performed this systematic review and meta analysis to assess the risk and clinical outcomes of COVID-19 in patients with rheumatic diseases compared with the general population. We searched PubMed, EMBASE, Scopus and Web of Science databases from Janu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
46
2
8

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(69 citation statements)
references
References 51 publications
(72 reference statements)
6
46
2
8
Order By: Relevance
“…By contrast, in a study from China, a higher incidence of COVID-19 in the general population as compared to ARD patients (0.0142 vs 0.0126%) [ 22 ] was found. Finally, a systematic review and meta-analysis of 26 observational studies showed that patients with ARD had an increased risk of developing COVID-19 compared with the general population [ 23 ]. In addition, although the possible role of ethnicity per se cannot be discarded, our higher rates could be explained by the fact that we identified cases over a longer period of time and we also included patients from the community many of whom had a mild COVID-19 disease [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, in a study from China, a higher incidence of COVID-19 in the general population as compared to ARD patients (0.0142 vs 0.0126%) [ 22 ] was found. Finally, a systematic review and meta-analysis of 26 observational studies showed that patients with ARD had an increased risk of developing COVID-19 compared with the general population [ 23 ]. In addition, although the possible role of ethnicity per se cannot be discarded, our higher rates could be explained by the fact that we identified cases over a longer period of time and we also included patients from the community many of whom had a mild COVID-19 disease [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Concerning previously described predictors of adverse course of COVID-19, we were able to corroborate the role of older age and chronic comorbidities (hypertension and neoplasm) as previously reported [ 15 , 26 , 31 36 ]. A recent meta-analysis found comorbidities (OR = 2.41, 95%; CI = 1.04–5.61; p = 0.041), hypertension (OR = 3.69; 95% CI = 1.41–9.69; p = 0.008), and lung diseases (OR = 2.93; 95% CI = 1.64–5.23; p = 0.000) significantly associated with hospitalizations [ 23 ]. We identified predictors of hospitalization; however, we were unable to do the same analysis for lethality due to the relatively small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, they may be at higher risk of COVID-19 [ 2 ]. Higher rheumatic disease activity can be a risk for severe disease [ 3 , 4 ]. Also, patients with RMDs have higher comorbidities or multi-morbidity that puts them at higher risk for COVID-19 [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…These findings may be of particular clinical value for individuals with autoimmune inflammatory rheumatic diseases (AIIRD) who by virtue of complex dysfunctional immune changes from their underlying diseases compounded by immunosuppressive therapies and a high prevalence of comorbidities appear to be at increased risk of infectious complications including acute respiratory viral infections and severe outcomes in COVID-19. 24 25 Importantly, the role of relative physical inactivity as a risk factor potentially contributing to these risks remains unexplored.…”
Section: Exercise and Infectious Diseasementioning
confidence: 99%